A CRITICAL ANALYSIS OF RASONADI KASHAYA IN ISCHEMIC STROKE - Baby, Christy; Chacko, James; Mishra, Ratnaprava; kumar K, Krishna (International Journal of Ayurveda and Pharma Research, 2016)
Stroke is undoubtedly a medical emergency, which even if properly managed can leave a person either physically or mentally crippled. Ischemic stroke is the most common form, where etiology of atherosclerosis had proven its link. The clinical features of stroke stands close to the disease Pakshaghata in Ayurveda and all Acaryas had given a detailed description regarding the Nidana (cause) Samprapti (pathogenesis) Bheda (types) & Chikitsa (treatment). Ischemic stroke may be related to Vata-kaphaja type of Pakshaghata as there is involvement of Srotorodha (obstruction). Hence the treatment aims include Vata-kapha samana (pacifying) measures, removing Srotorodha (obstruction), selecting drug having Katu rasa (pungent), Usna virya (hot potency) etc. Without provocation Pitta, Rasonadi kashaya explained for Vatavikaras (musculoskeletal, nervous disorders etc) contains Rasona (Allium sativum Linn), Pippali (Piper longum Linn.), Karavi (Carum carvi Linn.) and Sthira (Desmodium gangeticum) that satisfies the above properties. The drugs also possess Rasayana (nourishing /immunity /prevents recurrence) which is a good choice here as there is Dhatukshaya (catabolism of basic elements). Ayurvedic as well as modern analysis of the pharmacological properties of the drugs stands together with properties like anti-inflammatory, anti lipidemic, antiglycemic, antioxidant, anti microbial actions, thus proving beneficiary in both therapeutic and preventive aspects of ischemic stroke.